PROBLEMS OF THE LEGAL STATUS OF SELF-EMPLOYED CITIZENS (Conferencea, 2023)
This article will analyze the institution of self-employed citizens in our country. Despite the fact that every year the number of self-employed citizens in Russia increases, this institution is not clearly regulated by current legislation. It seems that the concept of self-employed citizens, the definition of the types of activities carried out by self-employed citizens and the fixation of their legal status should be reflected in the current legislation of our country.